2019
DOI: 10.1053/j.sodo.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic virtual treatment planning for functional esthetic results

Abstract: Virtual three dimensional (3D) facial diagnosis and treatment planning has the potential to improve outcomes for orthognathic surgery patients. It is necessary to appreciate the inadequacies of traditional two dimensional treatment planning and how that may adversely affect the virtual 3D treatment planning process. Virtual 3D planning greatly improves the clinician's ability to diagnose and treat facial form and position problems that prevent the patient from accomplishing the three Functional Facial Keys (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
10
0
5
Order By: Relevance
“…20,21 Postoperative analysis of the surgical outcome and treatment stability has proven valuable in refining surgical planning and execution. 34 For example, Gunson and Arnett 34 discussed how postoperative analysis helped them to discover new surgical techniques in order to overcome previously unobserved inaccuracies in their surgeries. In the systematic review and meta-analysis by Gaitan-Romero et al 4 , it was concluded that further high-quality studies utilizing standardized 3D methodologies are required.…”
Section: Maxillary Landmarks Anterior Nasal Spine (Ans)mentioning
confidence: 99%
“…20,21 Postoperative analysis of the surgical outcome and treatment stability has proven valuable in refining surgical planning and execution. 34 For example, Gunson and Arnett 34 discussed how postoperative analysis helped them to discover new surgical techniques in order to overcome previously unobserved inaccuracies in their surgeries. In the systematic review and meta-analysis by Gaitan-Romero et al 4 , it was concluded that further high-quality studies utilizing standardized 3D methodologies are required.…”
Section: Maxillary Landmarks Anterior Nasal Spine (Ans)mentioning
confidence: 99%
“…Традиционно все измерения пропорций выполняются на фотографиях и рисунках, измеряются не реальные расстояния, а их проекция на фронтальную плоскость, при этом проекция у плоского и выпуклого объекта одинакова. Поэтому в своих последних работах M.J. Gunson (2019) отказался от практики демонстрации послеоперационного результата в профиль и фас, мотивируя это тем, что только фотография в ¾ дает представление об истинном эстетическом результате [19]. С этой точки зрения поиск естественной горизонтальной плоскости и третьей оси координат является обоснованным.…”
Section: лицо как объемная фигураunclassified
“…Dentro de los procedimientos quirúrgicos es inherente considerar la importancia de la pérdida sanguínea intraoperatoria (PSI). La cirugía bucal y maxilofacial (CBMF), se encuentra en una permanente implementación y actualización de técnicas y procedimientos que contribuyen a disminuir tiempos operatorios, con una cirugía planificada (3D) y estructurada (1,2,3).…”
Section: Introductionunclassified
“…La cirugía ortognática (CO) es un procedimiento quirúrgico empleado para la corrección de las deformidades dentofaciales (DDF), cuya finalidad es alcanzar la función y estética a nivel del posicionamiento de los maxilares y la oclusión (1). Para ello existen diversas técnicas aplicadas a cada maxilar como las osteotomías tipo Le Fort I, II, III, la primera descrita por Bell et al, (4) para maxila, osteotomía sagital bilateral de rama (OSBR) descrita por Obwegeser con modificaciones como la de Wolford en 1987 para mandíbula (5,6) y la mentoplastía (7).…”
Section: Introductionunclassified